The Impact of Parents and Schools - Siraj, Iram; Mayo, Aziza (Cambridge : Cambridge University Press, 2014)
Social class is often seen as an intractable barrier to success, yet a number of children from disadvantaged backgrounds still manage to show resilience and succeed against the odds. This book presents the findings from fifty Child and Family Case Studies (CFCS) conducted with 13-16 year olds. The authors look specifically at the roles that people and experiences - at home, in schools and in the wider community - have played in the learning life-courses of these children; how these factors have affected their achievement; and explanations and meanings given by respondents to the unique characteristics, experiences and events in their lives. Featuring the voices of real parents and children, and backed up by a decade of quantitative data, this is a compelling record that will help readers to understand the complex nature of social disadvantage and the interplay between risk and protective factors in homes and schools that can make for a transformational educational experience.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).
Keywords: Social classes; Educational equalization